STAT: schema therapy for addiction treatment, a proposal for the integrative treatment of addictive disorders - Lacy, Elizabeth (Frontiers in Psychology, 2024)
The nature and origins of addictions and of their adjunctive behaviors, as well as their chronicity, call for treatments that conceptualize and treat them as the long-term and complex processes that they are. Addictions are often comorbid with personality problems (Casadio et al, 2014; Khantzian, 2003; Sher et al., 2000) and with trauma histories (Brady et al, 2004; Padykula & Conklin, 2010). Patients suffering from these disorders often show poor engagement with treatment and high rates of relapse (Van Den Bosch et al., 2007), possibly because available treatments have yet to address the patient suffering from addiction in a more integrated or holistic manner. In particular, comprehensive treatment models for addictive disorderslike treatments for personality disorders or traumaare likely to require the integration of behavioral, cognitive, and emotion-focused interventions within a facilitative therapeutic relationship (Farrugia et al., 2022; Robertson et al., 2021). However, most current treatment models, including ones which are highly effective in stabilization or behavioral change, lack one or more components of treatment that could sustain longer term recovery, wellness, and health for a higher percentage of patients (Ball et al., 1998; Fernandez-Montalvo et al., 2018).